Mechanical properties of novel out-of-plane steel beam–concrete wall pinned joints with T-shaped steel connectors under monotonic tension load. (1st August 2019) - Zhao, He; Nie, Xin; Zhu, Dan; Tao, Mu-Xuan
Highlights: A new form of steel beam-concrete wall joints with T-shape connectors is proposed. Tensile behaviour of the joint is researched by experimental and analytical method. The embedded depth of the connector significantly influences the joint behaviour. Breakout failure and web yield failure are two main typical failure modes. An analytical model for predicting pulling resistant capacity is proposed. Abstract: Nowadays, reinforced concrete core wall–steel frame hybrid structural systems are widely used in high-rise buildings. In this type of structural system, the steel beam–concrete wall (SBCW) joints bear significant cyclic tensile and compressive loads under earthquake motions. Considering that most of the compressive loads are transferred to the slabs rather than the joint core, the pulling resistant capacity of the joints plays a very important role in the seismic behaviour of the entire structure when neglecting the tensile strength contribution of concrete slabs. In this study, the pullout behaviour of a new form of SBCW pinned joints with T-shaped steel connectors was tested, and the load–displacement curves, failure modes, as well as stress and strain development of the specimens were analyzed. Two failure modes were observed in the experiments: one is the breakout failure mode characterized by the pullout of the concrete pyramid with lower strength and stiffness, and the other is the web yield failure mode characterized by the yielding of the web plate of the T-shaped steel connector with higher strength and stiffness. The failure mode that was experienced mainly depended on the embedded depth of the T-shaped steel connector. Then, an analytical model for predicting the pulling resistant capacity of the joint was proposed. In this model, the calculation method corresponding to the breakout failure mode, which is based on the principle of virtual work, can assess the respective contributions of concrete, shear studs and stirrups to the pulling resistance capacity of the joint, and the calculation method corresponding to the web yield failure mode is simplified by calculating the yield strength of the web plate of the T-shaped steel connector. Finally, the proposed model was verified by experimental results.